2020
DOI: 10.1051/kmae/2020010
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a large partial-depth guide wall to divert downstream migrating Atlantic salmon smolts at Tuilières dam, Dordogne River

Abstract: From 2010 to 2016, an evaluation of the performance of a partial-depth guide wall associated with three surface bypasses to ensure the safe downstream migration of Atlantic salmon smolts was conducted at the Tuilières power plant on the Dordogne River in southwestern France. The objectives of this study, during which 603 smolts were monitored using radio telemetry, were (i) to determine their escapement rate (passage through routes other than turbines), (ii) to analyse their behaviour faced with the structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Haro et al (1998) observed that maintenance of positive rheotaxis and strong swimming behaviour along the bypass system were important factors in bypass effectiveness. Previous studies have already mentioned lower overall bypass passage minimum efficiency rates (5%-28%: Chanseau et al, 1999;Gosset and Travade, 1999;Fjeldstad et al, 2012;Larinier et al, 2020) and some similar efficiency to our study (32%, Croze, 2008;33%: Chanseau et al, 2002;37.1%: Bosc et al, 2016in Tomanova et al, 2018. However, the most recent studies have quantified best performance ranging from 55% to 100% (reviewed in Tomanova et al, 2018).…”
Section: Tablesupporting
confidence: 84%
See 2 more Smart Citations
“…Haro et al (1998) observed that maintenance of positive rheotaxis and strong swimming behaviour along the bypass system were important factors in bypass effectiveness. Previous studies have already mentioned lower overall bypass passage minimum efficiency rates (5%-28%: Chanseau et al, 1999;Gosset and Travade, 1999;Fjeldstad et al, 2012;Larinier et al, 2020) and some similar efficiency to our study (32%, Croze, 2008;33%: Chanseau et al, 2002;37.1%: Bosc et al, 2016in Tomanova et al, 2018. However, the most recent studies have quantified best performance ranging from 55% to 100% (reviewed in Tomanova et al, 2018).…”
Section: Tablesupporting
confidence: 84%
“…Hence, the results obtained in this study do not represent a complete vision of what would have happened during the entire migration season of smolts in the Amblève River, especially under more important flow conditions. Finally, we used hatchery smolts, but as observed by Karppinen et al (2014), Renardy et al (2020) and Larinier et al (2020), they remain highly sensitive to the environmental cues that trigger fish migration. However, Larocque et al (2020) observed differences in survival between wild and hatchery smolts (better for wild) during downstream migration in a Lake Ontario tributary.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Ovidio et al (2017, Francis turbines) reported a research time of less than 1 h for the major proportion (70%) of the smolts. In large‐sized rivers, research time varied between 0.4 h (Larinier et al, 2020) and 4.7 h (Renardy et al, 2021) at hydropower stations equipped with Kaplan turbines. In our study, after choosing a migration route, the required median crossing time varied between 0.5 h and 2.4 h. The crossing speed was higher after passage over spillway gates than through Francis turbines or Archimedes screws.…”
Section: Discussionmentioning
confidence: 99%
“…Several other reasons, linked to bypass location and hydraulic conditions on the rack may, however, also explain this poorer performance. Firstly, with an angled rack, fish are guided toward the downstream end, where a full-depth bypass entrance should ideally be positioned (Courret and Larinier, 2008;Larinier et al, 2020). However, structural factors at the Pébernat intake led to a suboptimal bypass position (approximately 6 m downstream from the rack end), and design (a wide but shallow entrance), perhaps making the bypass less attractive.…”
Section: Performance With Closed Btgmentioning
confidence: 99%